The Evolving Role of the Inspectorate in Achieving a Sustainable Surabaya - Dasih, Tantri Sun Estuning; Indriana, Dina; Athfalina, Vidya Intani (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2025)
Purpose: to analyze the role of the Surabaya City Inspectorate in overseeing sustainable development policies and to identify challenges and opportunities that support the city's sustainability goals .  Method: using a qualitative approach with a longitudinal case study thematic analysis to explore in local government oversight practices. Results: strengthening the oversight function of the Inspectorate increases the effectiveness and accountability of sustainable city policies.. Novelty: provides a new perspective on optimizing the role of the Inspectorate through collaborative and technology-based oversight mechanisms. Contribution: collaboration with institutions, communities, and audit technology enhances early detection of irregularities and improves city governance efficiency Abstrak: Peran Inspektorat yang Berkembang dalam Mewujudkan Surabaya yang Berkelanjutan Tujuan: menganalisis peran Inspektorat Kota Surabaya dalam mengawasi kebijakan pembangunan berkelanjutan serta mengidentifikasi tantangan dan peluang yang mendukung tujuan keberlanjutan kota. Metode: menggunakan pendekatan kualitatif dengan studi kasus longitudinal dan analisis tematik untuk mengeksplorasi pola pengawasan pemerintah daerah.  Hasil: penguatan fungsi pengawasan Inspektorat meningkatkan efektivitas dan akuntabilitas kebijakan kota berkelanjutan. Kebaruan: memberikan perspektif baru tentang optimalisasi peran Inspektorat melalui mekanisme pengawasan yang kolaboratif dan berbasis teknologi. Kontribusi: kolaborasi dengan instansi, masyarakat, dan teknologi audit meningkatkan deteksi dini penyimpangan serta efisiensi tata kelola kota.